Partisipasi Masyarakat pada Penerapan Pembangunan Pariwisata Berkelanjutan (Studi Kasus Desa Wisata Pujon Kidul, Kabupaten Malang) - Widyarini Sistarukmi Ira; Muhamad Muhamad (Sekolah Vokasi, Universitas Gadjah Mada, 2019)
The development of sustainable tourism with tourism villages as its implementation has become one form of development that is considered in accordance with current needs, both from fulfilling economic needs as a parameter of the successful implementation of tourism development in the community and community involvement in tourism development in their area. This paper aims to record the form of implementation of the development of sustainable tourism in rural areas, with a focus on tourism villages seen from the impact of economic implications on income levels and shifts in people's livelihoods. Taking a case study in Pujon Kidul Tourism Village, Malang Regency. The research method was carried out by descriptive qualitative models and in-depth interviews. As a result, Pujon Kidul Tourism Village has succeeded in empowering the potential of its village through the development of sustainable tourism, as seen from the increased income of the community and the shift in the livelihood of agrarian communities to become entrepreneurs.